Analisis Faktor-Faktor yang Memengaruhi Penghimpunan Wakaf Uang di Indonesia (Pendekatan Analytical Network Process) - Khadijah Hasim; Deni Lubis; Khalifah Muhammad Ali (Department of Islamic Economics, IPB University, 2016)
Indonesia is a country with the largest Muslim population in the world. The potential of Islamic financial instruments grows among the society, and one of them is cash waqf. Cash waqf already have a complete law and legal institutions, but there is a gap between the potency and the real data of cash waqf raising. The aim of this research is to analyze the condition of cash waqf raising and the factors affecting the level of cash waqf raising in Indonesia. Using Analytical Network Process (ANP), the factors that affect the level of cash waqf raising are divided into three aspects namely institutional, society, and government. The results show that the institutional aspect has the biggest impact affecting the level of cash waqf raising and the three most influential factors are the focus of nazhir institutions, the understanding of society about cash waqf, and completeness of the cash waqf law.